Galicia is Burning: ‘Agrocuir’ in Opposition to the Metronormativity of ‘Queer’ - Barreto, Danny M. (Madrygal. Revista de Estudios Gallegos, 2020)
LGTB culture and politics tend to be associated with metropolitian urban centers. This article suggests that such ‘metronmativity’ characteristic of contemporary queer culture and politics has rendered invisible those LGTB communities in rural and non-metropolitan spaces in Galicia. As the field of queer studies undergoes an anti-urban and ecological turn, Galicia is a privileged site from which to reimagine LGTB politics. This piece surveys the emergent rural LGTB activism and cultural production which, to borrow the term from the Lugo-based collective, can be referred to as ‘agrocuir’. Far from being a local or isolated phenomenon, this anti-metronormative stance provides opportunities for thinking about queer Galician identity within a network of marginalized, racialized, non-hegemonic and rural queers.